Colchicine as a novel drug for the treatment of osteosarcoma through drug repositioning based on an FDA drug library - Oh, Jisun; An, Hyun−Ju; Yeo, Hyun Jeong; Choi, Sujin; Oh, Jisu; Kim, Segi; Kim, Jin Man; Choi, Junwon; Lee, Soonchul (Frontiers in Oncology, 2022)
Background: Colchicine is a traditional medication that is currently approved to treat gout and familial Mediterranean fever (FMF). However, colchicine has a wide range of anti-inflammatory activities, and several studies have indicated that it may be useful in a variety of other conditions, such as rheumatic disease, cardiac disease, and cancer. Osteosarcoma, the most common type of bone sarcoma, is derived from primitive bone-forming mesenchymal cells. In this study, we investigated whether colchicine could be used to treat osteosarcoma through the regulation of cell cycle signaling. Methods: Two human osteosarcoma cell lines, U2OS and Saos-2, were used. A clonogenic assay was used to determine the antiproliferative effects of colchicine on osteosarcoma cells. Reactive oxygen species (ROS) production and apoptosis were measured by flow cytometry. Migration and invasion assays were performed to investigate the inhibitory effects of colchicine. The signaling pathways related to colchicine treatment were verified by GO biological process (GOBP) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Results: Colchicine was selected as the lead compound based on the results of initial screening and cell viability assays conducted in Saos-2 and U2Os cells. Colchicine reduced the viability of Saos-2 and U2OS cells in a concentration-dependent manner. It also significantly inhibited colony-forming ability and induced ROS production and apoptosis. It also inhibited the migration and invasion of both Saos-2 and U2OS cells. GOBP and KEGG enrichment analyses indicated the involvement of microtubule-based processes and cancer-related pathways. Conclusions: These findings suggest that colchicine has therapeutic potential in osteosarcoma.